2014
DOI: 10.1177/1754045313515122
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining sexuality in menopause

Abstract: Sexual health in the menopause is a medical challenge because the progressive decline of sexual hormones interacts with the aging process and many psychosocial stressors modulate vulnerability for sexual symptoms (low sexual desire, poor arousal and lubrication, dyspareunia, orgasmic dysfunction and lack of satisfaction). In clinical practice, a coordinated approach is needed to optimally manage the risk for developing female sexual dysfunction (FSD), especially when chronic conditions are present. Biomedical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 94 publications
0
9
0
4
Order By: Relevance
“…Menopause is understood as a natural cessation of women’s reproductive ability. It typically occurs in women in late 40s and early 50s [ 3 ]. Therefore, conceiving a baby by women between older than 35 years old can be regarded as fertility in late reproductive age.…”
Section: Introductionmentioning
confidence: 99%
“…Menopause is understood as a natural cessation of women’s reproductive ability. It typically occurs in women in late 40s and early 50s [ 3 ]. Therefore, conceiving a baby by women between older than 35 years old can be regarded as fertility in late reproductive age.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the Socio-demographic factors impacting LSD and HSDD, various studies have reported different results. Some of these studies indicate that LSD and HSDD increase with age [7,9,10], Whereas in other studies, LSD has been the only factor associated with increasing age (not HSDD) [5].…”
Section: Hsdd Based On Research Data In the Diagnostic And Statistimentioning
confidence: 96%
“…Various studies have yielded different results regarding the socio-demographic factors affecting LSD and HSDD. Some of these studies indicated the increased risk of LSD and HSDD with advancing age [7,9,10], whereas in other studies, only LSD has been found to be associated with increasing age (not HSDD) [5].…”
Section: Introductionmentioning
confidence: 99%